Highly diversified crop–livestock farming systems reshape wild bird communities. Issue 2 (2nd December 2019) - Smith, Olivia M.; Kennedy, Christina M.; Owen, Jeb P.; Northfield, Tobin D.; Latimer, Christopher E.; Snyder, William E.
Abstract: Agricultural intensification is a leading threat to bird conservation. Highly diversified farming systems that integrate livestock and crop production might promote a diversity of habitats useful to native birds foraging across otherwise‐simplified landscapes. At the same time, these features might be attractive to nonnative birds linked to a broad range of disservices to both crop and livestock production. We evaluated the influence of crop–livestock integration on wild bird richness and density along a north‐south transect spanning the U.S. West Coast. We surveyed birds on 52 farms that grew primarily mixed vegetables and fruits alone or integrated livestock into production. Crop–livestock systems harbored higher native bird density and richness relative to crop‐only farms, a benefit more pronounced on farms embedded in nonnatural landscapes. Crop–livestock systems bolstered native insectivores linked to the suppression of agricultural pest insects but did not bolster native granivores that may be more likely to damage crops. Crop–livestock systems also significantly increased the density of nonnative birds, primarily European Starlings ( Sturnus vulgaris ) and House Sparrows ( Passer domesticus ) that may compete with native birds for resources. Models supported a small, positive correlation between nonnative density and overall native bird density as well as between nonnative density and native granivore density. Relative to crop‐only farms, on average, crop–livestock systems exhibited 1.5 times higher patch richness, 2.4 times higher density of farm structures, 7.3 times smaller field sizes, 2.4 times greater integration of woody crops, and 5.3 times greater integration of pasture/hay habitat on farm. Wild birds may have responded to this habitat diversity and/or associated food resources. Individual farm factors had significantly lower predictive power than farming system alone (change in C statistic information criterion (ΔCIC) = 80.2), suggesting crop–livestock systems may impact wild birds through a suite of factors that change with system conversion. Collectively, our findings suggest that farms that integrate livestock and crop production can attract robust native bird communities, especially within landscapes devoted to intensified food production. However, additional work is needed to demonstrate persistent farm bird communities through time, ecophysiological benefits to birds foraging on these farms, and net effects of both native and nonnative wild birds in agroecosystems.